THE PRACTICE OF FIELD SOCCER BY CHILDREN AND ADOLESCENTS WITH AGES BETWEEN 07 - 12 YEARS OLD, FROM THE CITY OF COLINA - SP. (Fiep Bulletin - online, 2014)
The most ontstanding sport modality in Brazil is soccer, therefore several children since early age live its practice. It has a special space in media and in the option of the population (mainly among parents that have low income). Soccer presently earns millions of reais, contributing to the glorious dream (to obtain status and fortune) for children and adolescents who can help financially their families in the future. They don't even imagine that very few reach this larget. The aim of this study was to understand the reasons that take children and adolescents to choose soccer and their expectations in relation to their performance. The applied methodology is of theoretical analysis - empiric through qualitative descriptive analysis (semi-structure interviews) with open questions to the youths and observing them in soccer classes and games. The sample was composed of 37 male children (18 from public school and 19 from private schools) with ages from 07 - 12 years old. The main data were that in public school professional and financial expectation of the young people with soccer were clearer than in private schools. The study in both places is the best form to help whole development of the interviewed. With results obtained in both places (two private schools and one public school), it is concluded that if young people in both places chose soccer as modality it is because they like it and that studies are a fundamental quality for the athlete. The existent difference is that in the public soccer school, some children and adolescents dream with a promising future in soccer.
Keywords: soccer school; expectations; financial future